Nunavut Land Claims Agreement
The Nunavut Land Claims Agreement is the largest and most prominent aboriginal land claim settlement in the Canadian history. When the Agreement was signed, legislation was also passed leading to the creation of a new territory called Nunavut on April 1, 1999. The new Canadian Territory was given the self rule government to serve both Inuit and non-Inuit in Nunavut.